Algoritma FCD dan NFT Pada Sistem Pencernaan Berbasis AR Menggunakan Single Marker - Akhmad Arief Mohajerani (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Humans were created with various systems that have different abilities, ranging from the respiratory system, digestive system, circulatory system and also the excretory system. From the weight of this skeleton there are various organs that also have different tasks. However, not a few people do not know anything about the skeleton and what organs are in the body, for example, what are the organs and functions related to the digestive system. In this study, we will focus on the organs in the human digestive system. To make it more interesting to study, the creators will introduce these organs as an augmented reality application. This exploration is aimed at providing an understanding of what organs and functions exist in the framework related to human digestion. In this study using a Single Marker strategy, with a system development model, namely the waterfall model consisting of analysis, design, implementation, testing and maintenance and using Fats Corner Detection (FCD) and Natural Future Trackingx (NFT). The results of the test with three devices, the closest distance to display objects is ±12 cm while the farthest distance is 80-100 cm. What's more, test results that depend on response times to render 3d articles on three devices took under 2 seconds.